2021
DOI: 10.3390/cancers13246368
|View full text |Cite
|
Sign up to set email alerts
|

Liver-Directed Therapy for Neuroendocrine Metastases: From Interventional Radiology to Nuclear Medicine Procedures

Abstract: Neuroendocrine neoplasms (NENs) are rare and heterogeneous epithelial tumors most commonly arising from the gastroenteropancreatic (GEP) system. GEP-NENs account for approximately 60% of all NENs, and the small intestine and pancreas represent two most common sites of primary tumor development. Approximately 80% of metastatic patients have secondary liver lesions, and in approximately 50% of patients, the liver is the only metastatic site. The therapeutic strategy depends on the degree of hepatic metastatic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 67 publications
0
21
0
1
Order By: Relevance
“…The importance of neuroendocrine liver metastases (NELM) in the survival of patients with advanced panNENs is represented not only by the fact that presence of liver metastases is associated with worse survival [ 11 , 70 , 155 , 162 , 337 , 338 , 339 , 340 , 341 ], but also by a significant correlation between the higher tumor burden of NELM and worse outcomes with PRRT [ 59 , 62 , 186 , 213 ], SSA [ 173 , 174 , 177 , 179 , 225 ], liver-directed therapy [ 342 ], and chemotherapy [ 321 ] ( Table 5 ). Several studies have reported the efficacy of liver-directed therapies including TACE/TAE and radio-embolization using 90 Y-labeled microspheres (selective internal radiotherapy [SIRT]), in controlling focal progression of NELM [ 69 , 70 , 71 , 72 , 74 , 341 , 343 ], as well as in controlling symptoms due to the liver metastases or hormone excess state of a F-panNENs [ 9 , 39 , 70 , 71 , 74 , 341 , 344 ]. The mean overall ORR to radio-embolization in a review of 12 studies including >400 patients with unresectable NELM was 55% (range 12–89%) and stable disease in 32% (range 10–60%) [ 9 ].…”
Section: Predictive Factors For Response To Liver-directed Therapies ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of neuroendocrine liver metastases (NELM) in the survival of patients with advanced panNENs is represented not only by the fact that presence of liver metastases is associated with worse survival [ 11 , 70 , 155 , 162 , 337 , 338 , 339 , 340 , 341 ], but also by a significant correlation between the higher tumor burden of NELM and worse outcomes with PRRT [ 59 , 62 , 186 , 213 ], SSA [ 173 , 174 , 177 , 179 , 225 ], liver-directed therapy [ 342 ], and chemotherapy [ 321 ] ( Table 5 ). Several studies have reported the efficacy of liver-directed therapies including TACE/TAE and radio-embolization using 90 Y-labeled microspheres (selective internal radiotherapy [SIRT]), in controlling focal progression of NELM [ 69 , 70 , 71 , 72 , 74 , 341 , 343 ], as well as in controlling symptoms due to the liver metastases or hormone excess state of a F-panNENs [ 9 , 39 , 70 , 71 , 74 , 341 , 344 ]. The mean overall ORR to radio-embolization in a review of 12 studies including >400 patients with unresectable NELM was 55% (range 12–89%) and stable disease in 32% (range 10–60%) [ 9 ].…”
Section: Predictive Factors For Response To Liver-directed Therapies ...mentioning
confidence: 99%
“…In several studies with TACE/TAE in patients with advanced NENs, the ORR was 25–85% and the symptomatic response was 50–100% [ 9 , 70 , 71 , 74 ]. In a recent systematic review [ 74 ] of embolization studies for neuroendocrine liver metastases (NELM) (101 studies, 5545 patients), the pooled partial response rate was 36.6%, 38.9% for stable disease, and 55.2% had a symptomatic response to treatment.…”
Section: Predictive Factors For Response To Liver-directed Therapies ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Darüber hinaus kommen die transarteriellen Verfahren, wie die transarterielle (Chemo-)Embolisation (TAE/ TACE) und die transarterielle Radioembolisation (TARE) mit Radioisotopen zur Anwendung. Die vielfältigen Möglichkeiten müssen sorgfältig abgewogen werden, um individuelle Therapieentscheidungen treffen zu können [37]. Die MWA geht im Vergleich zur RFA etwas schneller und erzeugt größere Ablationsareale, hat jedoch aktuell nur für die Behandlung hepatozellulärer Karzinome eine Überlegenheit im Vergleich zur RFA gezeigt [41].…”
Section: Nicht Chirurgische Lokoregionäre Therapieunclassified
“…In selected patients with LMs for whom hepatic surgery is contraindicated, percutaneous or intra-arterial treatments are safe and effective options for achieving disease control. Cazzato et al [ 8 ] provided a narrative review of the current knowledge on liver-directed therapy for LMs treatment, including both interventional radiology procedures and nuclear medicine options (90Y-Selective Internal Radiation Therapy (SIRT), Targeted Radionuclide Therapy) in NET patients.…”
mentioning
confidence: 99%